TOPOLOGICAL COMPARISON-BASED WORMHOLE DETECTION FOR MANET - Chan, King Sun; Alan, Mohammad Rafiqul (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Wormhole attack is considered one of the mostthreatening security attacks for mobile ad hocnetworks (MANET). In a wormhole attack, a tunnelis setup in advance between two colluders. Thecolluders record packets at one location and forwardthem through the tunnel to another location in thenetwork. Depending on whether or not the colludersare participating in the network functions, thewormhole attack can be further divided into twocategories: traditional wormhole attack andByzantine wormhole attack. Existing researchesfocusing on detecting traditional wormhole attackscan be classified into three categories: one-hop delaybased approach; topological analysis based orspecial hardware/middleware based approaches.Unfortunately, they all have their own limitations.Most of the researches detecting Byzantinewormhole attack are not addressing the Byzantinewormhole attack directly. Instead, they focus onobserving the consequence after a Byzantinewormhole attack, like packet dropping ormodification. In this paper, we propose to detectboth traditional and Byzantine wormhole attacks bydetecting some topological anomalies introduced bywormhole tunnels. Simulation results show that ourscheme can achieve both high wormhole attackdetection rate and accuracy. Our scheme is alsosimple to implement.KEY WORDS: Wormhole attack, Byzantine wormhole attack,manet, topological comparison.